ANALISIS HASIL BELAJAR DENGAN PENERAPAN MODEL PEMEBELAJARAN TEAM GAMES TOURNAMENT (TGT) DAN NUMBERED HEADS TOGETHER (NHT) PADA ELEMEN PENGELOLAAN KEARSIPAN DI KELAS XI MPLB SMK SWASTA BINA SATRIA MEDAN T.A 2025/2026 - Pakpahan, Yofanus; Tauada Silalahi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low learning outcomes of students in the Records Management element in Grade XI MPLB at Bina Satria Private Vocational High School Medan. The low learning outcomes were caused by the lack of varied and innovative learning models, resulting in students being less active during the learning process. This study aimed to determine the differences in learning outcomes between students taught using the Team Games Tournament (TGT) learning model and those taught using the Numbered Heads Together (NHT) learning model, as well as to identify the more effective model in improving students’ learning outcomes in Records Management. This research employed an experimental method with a two-experimental-class design. The population consisted of 78 students from classes XI MPLB 1 and XI MPLB 2. The sampling technique used was total sampling, in which the entire population was selected as the research sample. Class XI MPLB 1 was taught using the Team Games Tournament (TGT) learning model, while Class XI MPLB 2 was taught using the Numbered Heads Together (NHT) learning model. The research instrument was a learning outcomes test that had been tested for validity, reliability, difficulty level, and discrimination index. Data analysis was conducted through normality tests, homogeneity tests, and hypothesis testing using the Independent Sample t-test. The results showed that the average learning outcome of students taught using the TGT model was 46.75, while the average learning outcome of students taught using the NHT model was 81.38. The hypothesis test yielded a Sig. (2-tailed) value of 0.000 < 0.05, indicating a significant difference between the learning outcomes of students taught using the TGT and NHT models. Therefore, the Numbered Heads Together (NHT) learning model was found to be more effective than the Team Games Tournament (TGT) learning model in improving students’ learning outcomes in the Records Management element for Grade XI MPLB students at Bina Satria Private Vocational High School Medan in the 2025/2026 academic year